Psychiatric assessment in transplantation - Erick Messias; Christine E Skotzko (Universidade de São Paulo, 2000)
The implementation of the presumptive donor law in Brazil is expected to increase the availability of organs for transplantation. As medical management of end-stage organ dysfunction continues to improve, increasing numbers of potential transplant recipients will be available to meet this supply. There is mounting evidence that supports the involvement of skilled psychiatric practitioners in the selection of transplant candidates. Data supporting the influence of psychosocial factors on compliance and therefore medical outcomes continues to grow. The literature review allows delineating the components and rationale for comprehensive psychosocial evaluations as a component of preoperative transplantation evaluation.